Consumer Awareness and Beliefs Regarding Sustainable Products - Jerzy Żuchowski; Aleksander Lotko; Andrzej Chochół; Magdalena Paździor; Małgorzata Lotko (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: To identify consumer awareness and beliefs regarding sustainable products according to a consumer profile.